Kualitas Produk, Citra Merek dan Iklan terhadap Keputusan Pembelian Lipstik Revlon di Kota Ambon - Erlinda Tehuayo; Merry M. Pelupessy; Deasy Savana Ramadani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The aim of the research is to analyze the influence of product quality, brand image and advertising on purchasing decisions for Revlon lipstick in Ambon city. This research is quantitative descriptive research. The population in this study were consumers who used Revlon lipstick in Ambon city. The sample in this study was 100 respondents. By using a questionnaire as a data collection tool. Sampling used purposive sampling technique. The data analysis method used is Multiple Linear Regression. Based on the results of the multiple regression test, it shows that the product quality variable (X1) has no effect on consumer purchasing decisions (Y). This is proven by the results of multiple linear regression testing which was obtained at 0.024. Furthermore, the brand image variable (X2) has a positive and significant influence on consumer purchasing decisions (Y). This is proven by the results of multiple linear regression testing of 0.241 and the advertising variable (X3) has a positive and significant influence on consumer purchasing decisions (Y). This is proven by the results of multiple linear regression testing which was obtained at 0.322.